Ethical Discourse on Artificial Intelligence in Media Reporting A Critical Discourse Analysis (CDA) Approach - Nadya Hafizah Harahap; Ridha Khairani; Muhammad Hilmy Zhafran; Muhammad Natsir (CV. Rayyan Dwi Bharata, 2026)
The rapid development of artificial intelligence (AI) within the digital media landscape has generated increasingly complex ethical discourses, not only at the level of policy and institutional frameworks but also within the everyday experiences of users. This phenomenon is significant as media functions not merely as a channel of information, but as a powerful force shaping how individuals interpret, experience, and negotiate the meaning of technology in social life. This study aims to explore how ethical discourses surrounding AI in media coverage are interpreted through individuals’ subjective experiences. Employing a qualitative approach with an interpretative phenomenological design, data were collected through in-depth interviews, digital observation, and document analysis involving ten participants who are active social media users. Data analysis was conducted using thematic analysis integrated with a Critical Discourse Analysis (CDA) perspective. The findings reveal three central patterns: ethical ambivalence between convenience and anxiety, tensions between media framing and personal experience, and the negotiation of identity and self-value in the context of AI advancement. These results indicate that AI ethics is not merely understood as a normative construct, but as a lived and dynamic experience shaped by contradictions and ongoing meaning-making processes. Theoretically, this study extends CDA by incorporating the dimension of subjective experience into discourse analysis. Practically, it offers implications for strengthening critical digital literacy, developing more context-sensitive policies, and designing educational frameworks that are responsive to the ethical challenges of emerging technologies. Furthermore, this study opens new avenues for exploring the interconnections between technology, discourse, and identity formation in the digital era.